AB0219 Down's Arthropathy (DA): Features of Inflammatory Arthritis in Children with Trisomy 21. (9th June 2015) - Foley, C.; Killeen, O.; MacDermott, E.; Veale, D.
Abstract : Background: The "Arthropathy of Down syndrome" was first reported in 1984. To date the largest case series for reference is a retrospective chart review of 9 children with Trisomy 21 (T21) & arthritis, reported in 1990. There are no published population surveys. Crude estimates suggest the incidence of arthritis in T21 is as much as 3-6 fold greater than JIA in the general paediatric population. Prevalence has been estimated to be 8.7/1000. Despite these suspected higher incidence & prevalence rates, arthritis is rarely recognised at onset, & remains under-diagnosed in this population group. It is unknown whether arthritis in children with T21 represents JIA or is a unique arthropathy in light of the genetic & immunologic abnormalities associated with T21. Objectives: – To perform a musculoskeletal examination on children with T21 aged 0-20 years – To investigate & manage newly diagnosed DA cases as per normal clinical practice for JIA. Methods: Children with T21 were invited to attend a screening clinic. Screening involved completion of a health questionnaire & a comprehensive musculoskeletal examination. DA cases detetected were invited to attend the NCPR for investigation & management as per normal clinical practice. Data on a convenience sample of 33 newly diagnosed children with JIA was collected to create a comparison group. Results: To date, 503 children with T21 have been screened for DA. 22 new cases have been diagnosed during the time frame of the study. All of these children had poor language skills or were non-verbal. Only 11% of the parents suspected that their child may have arthritis prior to attending our screening clinics, and this was only after reading our recruitment literature. In total, we now have 33 children attending the NCPR with DA (combining cases attending pre-dating the start date of the study). This suggests the prevalence of DA in Ireland is 18-21/1000. The majority of children presented with a polyarticular pattern of disease. All were RF & ANA negative. No cases of uveitis have been observed to date. 88% of the DA cohort had small joint involvement of the hands, significantly higher than that observed in the JIA comparison group. Erosive changes were reported on X-Ray in 29.2% of the DA cohort (9.5% JIA Cohort). MTX nausea was a significant barrier to treatment with this DMARD in DA. There was a significant delay in diagnosis of DA, 1.7 years v 0.7 years in the JIA cohort. Conclusions: Children with T21 are at increased risk of developing arthritis. There is a lack of awareness of this risk among health care professionals & the general public at large. This almost certainly contributes to poor recognition of the disease and a delay in diagnosis. The predominant pattern of disease is polyarticular small joint arthritis. Treatment with standard protocols used in JIA is complicated by drug-associated side effects in children with T21. However, a good response to treatment with steroid joint injections has been observed. Our study has raised a number of questions. Future research to accurately define this disease & identify best practice with regards to treatment would be invaluable. References: The arthropathy of Down syndrome: an underdiagnosed & under-recognised condition; Juj H, Emery HJ; J Pediatr 2009 Feb;154(2):234-8 Acknowledgements: National Children's Research Centre, OLCHC, Dublin Education Research Centre, St Vincent's University Hospital, Dublin Children and their familes Disclosure of Interest: None declared